PRODUKTIVITAS BONGKAR MUAT DAN WAKTU SANDAR KAPAL PELABUHAN TANJUNG EMAS - Denny J Najoan; Deshalena Ayu Rachma Putri; Siti Nurhayati (Institut Transportasi dan Logistik Trisakti, 2017)
The objective of this research is to find out how big the influence of the loading and unloading productivity and the berthing time in a case study at Tanjung Emas Port, Semarang. The data analysis method used was simple linear analysis and hypothesis test. This research used secondary data of loading and unloading productivity (BCH) and berthing time in a year. The analysis results and discussion show that there is a proportional influence of loading and unloading productivity and berthing time that is shown in equation of simple linear regression line of Y = 35,38 - 0,832X. Furthermore, the hypothesis test results show that F count = 11.36 and F table = 4.96 , therefore, F count > F table or 11.36 > 4.